Heterogeneous Government Spending Multipliers in the Era Surrounding the Great Recession - Bernardini, Marco; De Schryder, Selien; Peersman, Gert (The Review of Economics and Statistics, 2020)
We use novel quarterly data of U.S. states to examine the dynamics of relative spending multipliers in the decade surrounding the Great Recession. While multipliers were around 1 in expansions, they reached values above 4 when a state was in a recession. Also a high (low) degree of household indebtedness augmented (lowered) a state's multiplier by 0.5 in expansions and 2 in recessions. We further document modest positive spillover effects across states and show that a mere redistribution of spending across states also had a significant influence on the aggregate U.S. economy due to cross-state heterogeneity of the effects.